Hotel Image and Trust in Guest Loyalty Relationships: A Study in Universitas Negeri Padang Hotel Padang City - Lisna, Yuke Permata; Yuricha, Stephanie Vivian; Maharani, Tiara; Arif, Ahmad (JURNAL PENDIDIKAN DAN KELUARGA; Vol 15 No 01 (2023): Jurnal Pendidikan dan KeluargaDO - 10.24036/jpk/vol15-iss01/1287, 2023)
The continued development of tourism encourages the growth of the tourism industry and promotes competitive tourism. Creating a loyal customer base is necessary for each destination to exist and be sustainable. This study identifies factors that drive customer loyalty, such as hotel image and guest trust. This study also examines the role of switching costs as a moderating variable that can intervene in the influence of each antecedent variable on hotel guest loyalty. This study involved UNP Hotel guests as a sample with criteria aged over 17 years who had stayed at the hotel (purposive sampling). The analysis was carried out using a variant-based structural equation model approach (variant-based SEM) with two stages, namely the Inner Model and the Outer Model. The outer model is used to test the quality of the instrument, while the inner model is used to test the hypothesis. Based on the results of the data analysis, it was found that switching costs play a role in the correlation between hotel image, trust, and hotel guest loyalty.